Match Success Trends in United States Ophthalmology Residency Programs - Driver, Todd H.; Loh, Allison R.; Yu, Fei; Pletcher, Steven D.; Naseri, Ayman (Journal of Clinical & Academic Ophthalmology, 2016)
Background Medical students in the United States are inconsistently exposed to ophthalmology. Not only is this eroding U.S. medical graduates' ability to diagnose and treat ophthalmologic conditions, it may potentially affect interest in the specialty.Methods To assess medical student's interest in pursuing ophthalmology training, this study sought to evaluate the match rate trend among U.S. medical school seniors applying into a U.S. ophthalmology residency and compare the trend to another traditionally competitive surgical subspecialty, otolaryngology (ENT).Results From 2009 to 2013, the rate of successful residency matching for ophthalmology increased (12% increase per year in the odds of matching [95% CI: 1.04, 1.20]), while the ENT match rate decreased (7% decrease per year in the odds of matching (95% CI: 0.87–0.99). The ophthalmology match rate increased despite the fact that the expansion in the number of graduating U.S. medical students outpaced the increasing number of ophthalmology and ENT residency positions.Conclusion The increasing match rate in ophthalmology is surprising and suggests that U.S. medical student's interest in ophthalmology may be waning. Future investigations are needed to determine the reasons behind the increasing match rate and the potential decreasing interest of medical students toward ophthalmology.
Keywords: ophthalmology residency; match rate; medical education